A few questions about certain paths of French phenomenology inspired by reading Przemysław Zgórecki’s book entitled "Czasowość eschatologiczna. Fenomenologia Jean-Yves Lacoste’a" (WT UAM, Poznań 2022) - Stachewicz, Krzysztof (Filozofia Chrześcijańska, 2023)
Book review: A few questions about certain paths of French phenomenology inspired by reading Przemysław Zgórecki's book entitled "Czasowość eschatologiczna. Fenomenologia Jean-Yves Lacoste’a" (WT UAM, Poznań 2022)